2022
DOI: 10.1177/2333794x221079550
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Pre-Lacteal Feeding Practices Among Mothers Having Children Aged 0-36 Months in Bangladesh: Evidence From Bangladesh Demographic and Health Survey 2017-18

Abstract: Despite being a known barrier to optimal breast-feeding indicators, the practice of Pre-lacteal Feeding (PLF) remains a key challenge in Bangladesh. This study examines the prevalence and underlying factors associated with PLF, for which data from a weighted sample of 4982 Bangladeshi mothers with children aged 0 to 36 months from the 2017-18 Bangladesh Demographic and Health Survey was used. Step-by-step multivariate logistic regression was performed to identify the association of significant determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Overall, one in ten (10%) women had ever introduced prelacteal feeds to their newborn infants. Our finding is similar to the proportion found in studies conducted in East Africa (12%) [21] and Ethiopia (14%) [16,42], but much lower than findings found in studies conducted in other Asian LMICs (33.9%) [17], including Bangladesh (29%) [31], Nepal (30.6%) [29], and Indonesia (45%) [43]. Reasons for the differences in the rates of prelacteal feeding may be due to sociocultural factors, geographical settings, maternal health service use or availability, and access to media and information across different countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, one in ten (10%) women had ever introduced prelacteal feeds to their newborn infants. Our finding is similar to the proportion found in studies conducted in East Africa (12%) [21] and Ethiopia (14%) [16,42], but much lower than findings found in studies conducted in other Asian LMICs (33.9%) [17], including Bangladesh (29%) [31], Nepal (30.6%) [29], and Indonesia (45%) [43]. Reasons for the differences in the rates of prelacteal feeding may be due to sociocultural factors, geographical settings, maternal health service use or availability, and access to media and information across different countries.…”
Section: Discussionsupporting
confidence: 88%
“…A population-based analysis of 57 participating countries found that prelacteal feeding remained prevalent in LMICs, with Asia having the highest prevalence (nearly 60%) compared to other regions (<40%) [28]. Similarly, recent studies in the Asia-Pacific, such as Bangladesh, Nepal, and Pakistan, showed high prelacteal feeding rates (29%, 30.2%, and 32%, respectively) [2931]. Such forms of supplementation can be particularly deleterious in settings where poverty or resource scarcity can impede nutritional potential.…”
Section: Introductionmentioning
confidence: 99%